2020
DOI: 10.48550/arxiv.2003.04056
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Variational Time Discretizations of Higher Order and Higher Regularity

Simon Becher,
Gunar Matthies

Abstract: We consider a family of variational time discretizations that are generalizations of discontinuous Galerkin (dG) and continuous Galerkin-Petrov (cGP) methods. The family is characterized by two parameters. One describes the polynomial ansatz order while the other one is associated with the global smoothness that is ensured by higher order collocation conditions at both ends of the subintervals. The presented methods provide the same stability properties as dG or cGP. Provided that suitable quadrature rules of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Further numerical studies for the wave equation can be found in [11,5]. For the application of the Galerkin-collocation to mathematical models of fluid flow and systems of ordinary differential equations we refer to [4,15,16]. In the numerical experiments, the Galerkin-collocation schemes have proved their superiority over lower-order and standard difference schemes.…”
Section: Introductionmentioning
confidence: 99%
“…Further numerical studies for the wave equation can be found in [11,5]. For the application of the Galerkin-collocation to mathematical models of fluid flow and systems of ordinary differential equations we refer to [4,15,16]. In the numerical experiments, the Galerkin-collocation schemes have proved their superiority over lower-order and standard difference schemes.…”
Section: Introductionmentioning
confidence: 99%